Amorphous Alloy: Promising Precursor to Form Nanoflowerpot. (20th May 2014) - Lan, Guo; Xie, Zhiqiang; Huang, Zhenwei; Yang, Shengchen; Zhang, Xuhai; Zeng, Yuqiao; Jiang, Jianqing
Abstract : Nanoporous copper is fabricated by dealloying the amorphous Ti2 Cu alloy in 0.03 M HF electrolyte. The pore and ligament sizes of the nanoporous copper can be readily tailored by controlling the dealloying time. The as-prepared nanoporous copper provides fine and uniform nanoflowerpots to grow highly dispersed Au nanoflowers. The blooming Au nanoflowers in the nanoporous copper flowerpots exhibit both high catalytic activity and stability towards the oxidation of glucose, indicating that the amorphous alloys are ideal precursors to form nanoflowerpot which can grow functional nanoflowers.